IMPLEMENTASI MATA KULIAH KEWIRAUSAHAAN DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Ostin Y Usman; Imam Mashudi (LPPM Universitas Muhammadiyah Gorontalo, 2025)
This study aims to analyze the implementation of the Entrepreneurship course at Universitas Muhammadiyah Gorontalo (UMGo) within the framework of Outcome Based Education (OBE) and the Merdeka Belajar–Kampus Merdeka (MBKM) program. A descriptive qualitative approach was employed through interviews with faculty deans, course lecturers, and the Director of the University-Owned Business Entity (BUMK). The findings reveal that the Entrepreneurship course has been integrated across all study programs at UMGo as a means of developing students’ creativity, innovation, and self reliance. Implementation is carried out through practice-based learning, including the establishment of the Faculty of Social Sciences Café (KAFEIS), the formation of Student Business Groups (KUM), product exhibitions, and student participation in campus entrepreneurship programs. The main challenges identified include limited raw materials, lack of student capital, and differing perceptions between lecturers and the quality assurance unit regarding OBE-based learning. As strategic steps, the university has developed inter-faculty collaboration, utilized local resources, and strengthened the role of BUMK as a business incubation center for students. This study concludes that the success of entrepreneurship education depends on the synergy between institutional policies, resource support, and practice-oriented learning approaches that foster independence and innovation.